Efficacy and safety of camostat mesylate in early COVID-19 disease in an ambulatory setting: a randomized placebo-controlled phase II trial. (September 2022) - Tobback, Els; Degroote, Sophie; Buysse, Sabine; Delesie, Liesbeth; Van Dooren, Lucas; Vanherrewege, Sophie; Barbezange, Cyril; Hutse, Veronik; Romano, Marta; Thomas, Isabelle; Padalko, Elizaveta; Callens, Steven; et al.
Highlights: Treatment with camostat did not affect the cycle threshold change in the early phase of COVID-19 disease. Clinical improvement was similar in patients with COVID-19 treated with camostat or a placebo. Treatment with camostat did not affect the SARS-CoV-2 neutralizing antibody response. This randomized controlled trial showed the safe use of 300 mg camostat three times daily in patients with COVID-19. Camostat mesylate is not effective as an antiviral drug for ambulatory patients with COVID-19. Abstract: Objectives: This study aimed to assess the efficacy and safety of 300 mg camostat mesylate three times daily in a fasted state to treat early phase COVID-19 in an ambulatory setting. Methods: We conducted a phase II randomized controlled trial in symptomatic (maximum 5 days) and asymptomatic patients with confirmed COVID-19 infection. Patients were randomly assigned in a 2:1 ratio to receive either camostat mesylate or a placebo. Outcomes included change in nasopharyngeal viral load, time to clinical improvement, the presence of neutralizing antibodies, and safety. Results: Of 96 participants randomized between November 2020 and June 2021, analyses were performed on the data of 90 participants who completed treatment (N = 61 camostat mesylate, N = 29 placebo). The estimated mean change in cycle threshold between day 1 and day 5 between the camostat and placebo group was 1.183 ( P = 0.511). The unadjusted hazard ratio for clinical improvement in the camostat group was 0.965 (95% confidence interval, 0.480-1.942, P = 0.921 by Cox regression). The percentage distribution of the 50% neutralizing antibody titer at day 28 visit and frequency of adverse events were similar between the two groups. Conclusion: Under this protocol, camostat mesylate was not found to be effective as an antiviral drug against SARS-CoV-2. Trial registration: ClinicalTrials.gov NCT04625114 ; November 12, 2020.